Confluence of newborn's sex and their mother's characteristics resulting in fetal macrosomia among Indian neonates - Priya Das; Subhadeep Saha; Tanu Das; Partha Das; Tamal Basu Roy (Pediatrics and Neonatology)
Background: A newborn's birth weight ≥4000 g is defined as fetal macrosomia, which is recognized as a reproductive and serious child health concern. Objectives: Our study aims to reveal existence of any connection between maternal factors and newborn sex in giving birth to newborn ≥4000 g in an Indian context. Methods: Data were drawn from the fifth round of National Family Health Survey (NFHS-5). A cross-sectional observational study was carried out with a total of 152,827 children born to women in reproductive age group (15–49) who had most recent live birth in the five years preceding the survey. Descriptive analyses, cross-tabulation, test of association and multivariate logistic regression analyses were performed. Results: In India, the prevalence of macrosomia was found in 3.8% of the total study participants. Considering newborn characteristics, fetal macrosomia was more prevalent among male neonates than female (AOR: 0.730; 95% CI: 0.687–0.775). Regarding maternal characteristics, overweight (AOR: 1.468; 95% CI: 2.042–2.559) and obese (AOR: 2.764; 95% CI: 2.394–3.192) motherswith gestational diabetes (AOR: 1.731, 95% CI: 1.385–2.164) and hypertension (AOR: 1.288, 95% CI: 1.116–1.488) were more likely to giving birth of macrosomic babies. Multiparous mothers (AOR: 1.207, 95% CI: 1.128–1.293) and women who did not undergo proper antenatal care (ANC) follow up had also greater risk of developing fetal macrosomia. Muslim women (AOR: 1.223, 95% CI: 1.119–1.338), and women belonging to a tribe (AOR: 1.476, 95% CI: 0.922–2.361) were significantly associated with the risk of having newborn ≥4000 g. Conclusion: Emphasis should be given on counseling for mothers for desired weight management before and during pregnancy, gestational diabetes and hypertension screening, physical activity during pregnancy, adequate ANC follow up and balanced dietary intake among pregnant women.